Management analysis of motivation and satisfaction in individual and team sports - Nugroho, Agung; Lismadiana, Lismadiana; Hastuti, Tri Ani (Jorpres (Jurnal Olahraga Prestasi), 2023)
This research aims to analyze: (1) the influence of service quality on motivation in individual and team sports; (2) the influence of service quality on satisfaction in individual and team sports; (3) financial influence on motivation in individual and team sports; (4) financial influence on satisfaction in individual and team sports. This type of research is quantitative, correlational research with survey methods. The collection technique uses interviews and questionnaires which are distributed to respondents via Google Form, the instrument uses a Likert Scale. The research population was athletes and coaches of the PON regional training center, with a total sampling technique of 137 respondents. The sample consists of 31 individual and team sports. The data analysis technique uses Structural Equation Modeling (SEM) with a PLS approach. The results of research on individual sports are: (1) service quality has a positive and significant effect on motivation; (2) service quality has a positive and significant effect on satisfaction; (3) finances have a positive but not significant effect on motivation; (4) finances have a positive and significant effect on satisfaction. Meanwhile, the results of research on team sports are: (1) service quality has a positive and significant effect on motivation; (2) service quality has a positive and significant effect on satisfaction; (3) finances have a significant negative effect on motivation; (4) finances have a positive and significant effect on satisfaction. It was concluded that to motivate regional training center athletes by improving management, especially in service quality, finances for individual sports and team sports. It is necessary to pay attention that team sports have a more complex character such as; the number of athletes is greater, the need for greater equipment, the risk of injury, and the dominant teamwork factor, compared to individual sports which have a higher level of stress. In providing financial assistance between individual sports and team sports, KONI DIY does not need to differentiate, because the research results have no significant influence on the motivation of athletes at regional training center. Improving financial management at the KONI regional training center will have an impact on athlete satisfaction, which is expected to improve athlete performance.